Ancient zinc smelting in the Upper and Middle Yangtze River region. (June 2020) - Li, Yuniu; Xiao, Birui; Juleff, Gill; Huang, Wan; Li, Dadi; Bai, Jiujiang
Abstract: Abstract : Here the authors report on a project that aims to understand zinc-production technologies at the earliest zinc-smelting site in China. Excavations at the site of Linjiangerdui, south of the Yangtze River, have provided a chronological sequence for smelting sites and revealed new evidence for methods of production.